Design and Development of Resource Repository for Grid Environment - Sharma, Rohit (My University, 2008)
Grid is a collection of distributed computing resources available over a local or wide area network that appears to an end user or application as one large virtual computing system. Resource management is central to the operation Grid. The first step in resource management is discovery of desired resources. It is the process that takes as input a user request and returns a list of resources or services that can possibly fulfill the given request. Resource Discovery in Grids is critical for efficient resource allocation and management. Grid middleware provides administrators with seamless computing ability and uniform access to resources in the heterogeneous Grid environment. They are software stacks designed to present disparate compute and data resources in a uniform manner. But different middleware have their own mechanism and policy to discover resources in Grid. For example Globus uses MDS, Condor has a match making algorithm to discover the resources whereas Alchemi.NET works on First Come First Serve basis. Problem of heterogeneity further hinders the process of resource discovery. A good Resource Repository which stores the relevant information about Grid clusters can help very much in resource discovery and further in resource management process. This thesis proposes a Resource Repository which is user friendly and has relevant information of Grid Cluster of Alchemi.NET and Globus, and its centralized structure helps in better management and monitoring of a Grid environment.
M.E. (Software Engineering)
Keywords: Resource Discovery; Resource Repository; Grid Computing